1990
DOI: 10.1116/1.576516
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of electrowetting-based microactuation

Abstract: Electrical control of the interfacial tension between a liquid and solid ("e1ectrowetting") has been studied as a means of actuation in the microdomain (characteristic dimensions 1 fim-l mm). Electrowetting provides a means of direct fluid pumping with no moving mechanical parts, which may prove useful in a number of application areas, most notably the liquid cooling of high-density microelectronic devices. A detailed model of a test device for the study of e1ectrowetting is presented. The model describes liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 0 publications
0
57
0
Order By: Relevance
“…͑22͒ until some critical voltage V c , at which point electrowetting saturates. ͓Recently, however, Krupenkin et al ͑2004͒ demonstrated that a superhydrophobic nanostructured surface becomes completely wet with only 22 V.͔ More generally, the saturation mechanism remains unknown ͑Quilliet and Berge, 2001;Moon et al, 2002͒, although Mach et al, 2002;Acharya et al, 2003;Hsieh et al, 2003͒. Specific microfluidic examples include electrowettingbased micropumps ͑Colgate and Matsumoto, 1990;Jun and Kim, 1998;Yun et al, 2002͒, creation, manipulation, and metering of fluid droplets ͑Lee and Pollack et al, 2000;Lee, Moon, et al, 2002;Cho, Moon, and Kim, 2003;Kuo et al, 2003;Ren et al, 2004͒, and chemical …”
Section: Electrowettingmentioning
confidence: 99%
“…͑22͒ until some critical voltage V c , at which point electrowetting saturates. ͓Recently, however, Krupenkin et al ͑2004͒ demonstrated that a superhydrophobic nanostructured surface becomes completely wet with only 22 V.͔ More generally, the saturation mechanism remains unknown ͑Quilliet and Berge, 2001;Moon et al, 2002͒, although Mach et al, 2002;Acharya et al, 2003;Hsieh et al, 2003͒. Specific microfluidic examples include electrowettingbased micropumps ͑Colgate and Matsumoto, 1990;Jun and Kim, 1998;Yun et al, 2002͒, creation, manipulation, and metering of fluid droplets ͑Lee and Pollack et al, 2000;Lee, Moon, et al, 2002;Cho, Moon, and Kim, 2003;Kuo et al, 2003;Ren et al, 2004͒, and chemical …”
Section: Electrowettingmentioning
confidence: 99%
“…where γ sl0 corresponds to zero charge condition and c is the capacitance per unit area assuming that the charge layer can be modelled as a symmetric Helmholtz capacitor [12]. To best characterize the microlens array we positioned the hotplate with the sample in a Digital Holographic Microscope as it's drawn in Fig.3.…”
Section: Methodsmentioning
confidence: 99%
“…The hydrostatic pressure is responsible for changing the focal power of the microfluidic lens. Electro-wetting or more in general studies on wettability and de-wettability [11][12][13][14][15][16][17][18][19][20][21][22] of surfaces have been studied and investigated since long time with the aim to pattern liquids on surfaces. An interesting overview about scope, methods and results is given in ref.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) The change in the wettability of the fluid has been confirmed to be reversible at low voltages, for example, for a droplet of liquid metal (mercury) 2) or a droplet of 10 À2 M KNO 3 electrolyte 3) on various dielectric films. By using this technique, many applications have been recently achieved in micro-actuation, 2,4,5) micro-fluidic transport and mixing, 6,7) switchable devices, 8,9) liquid lens profile control [10][11][12] and self-assembled particle arrays.…”
Section: Introductionmentioning
confidence: 95%